Acute kidney injury is under-recognised and under-reported in hospitalised patients in Australia - Mitchell, T.; Feher, E.; Mitchell, G.; Chakera, Aron (Blackwell Publishing, 2017)
Acute kidney injury (AKI) in hospitalised patients is associated with adverse outcomes; however, it remains unrecognised and under-reported. A total of 48 045 serum creatinine results from 8129 tertiary hospital inpatients were reviewed. The prevalence of AKI was 4.33%. Mortality was significantly higher in patients with AKI (16.76%) compared to those without AKI (1.88%, P < 0.001). Documentation of AKI in discharge summaries was poor.